Seismic design and performance evaluation of typical lightweight and heavyweight RC girder bridges with friction pendulum bearing in Indonesia. (December 2022) - Moestopo, Muslinang; Imran, Iswandi; Siringoringo, Dionysius M.; Michael, James; Lim, Erwin; Yamazaki, Shinsuke
Abstract: Seismically isolated bridges have shown better seismic performance than bridges with conventional bearings during large earthquakes. While elastomeric type of isolation has been introduced in various new highway bridges in the country, the use of friction pendulum system for bridge bearing is not yet common in Indonesia, a highly seismically active country. In this paper, design and seismic performance evaluation of two typical reinforced concrete bridges seismically isolated by single concave friction pendulum (SCFP) bearings system and designed according to Indonesian seismic code is described. The reference bridges are selected from typical light rapid transit (LRT) bridge and highway reinforced concrete (RC) bridge in Indonesia. Seismic performances of SCFP-isolated bridges with different bearing configurations and the conventional non-isolated bridges under 1000-year design earthquake were investigated and compared using nonlinear finite element analyses. The results show that SCFP-isolated bridges performed better than non-isolated bridges under design earthquake as shown by reductions in the base shear force, absolute deck acceleration, and deck acceleration amplification ratio. Effects of SCFP on the seismic performance of isolated bridge was evaluated by comparing the moment and rotation values of each pier and the possible formation of plastic hinges. Performance comparisons of SCFP-isolated bridges with various friction types and arrangements revealed that the LRT bridge with all higher friction and the highway bridge with lower friction have the best seismic performance among all isolated bridge models analyzed.